Analisis Pengaruh Faktor-Faktor Demografis dan Personal dalam Minat Mahasiswa Sekolah Vokasi Universitas Diponegoro terhadap Penggunaan Bank Digital - Muhammad Azhar Al Fajri (JUMBIWIRA : Jurnal Manajemen Bisnis Kewirausahaan, 2025)
This study aims to analyze the influence of demographic and personal factors on the interest of Vocational School students at Diponegoro University in using digital banking services. The research problem focuses on whether variables such as age, Grade Point Average (GPA), semester, region of origin (urban/rural), allowance, ICT literacy, and side business have a statistically significant contribution to variations in digital banking interest. A quantitative approach with a descriptive-correlational design was employed, and the research was conducted in June 2025. A total of 117 active vocational students with prior digital banking experience were selected using purposive sampling. Data were collected via online questionnaires and analyzed using binary logistic regression through SPSS software. The results show that none of the seven demographic and personal variables had a statistically significant influence (p > 0.05) on students’ interest in using digital banking. This finding indicates that these individual characteristics are not dominant determinants of interest. Rather, students’ interest in digital banking appears to be widespread and driven by functional needs in daily life. Consequently, this study recommends further exploration of other factors such as attitude, perceived ease of use, perceived usefulness, and trust in future analytical models.